(3QSGdI GHf SjfG dCHi LYaQ GdcjGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdeSFdI GdChdi Ydi eG GhQOg GdSGFd HdaXg bGd Gf GdfGQ dCfgG eQcHI ef hUhQI hcd eQcH efg s
(3BNQgG (B:s
(3dCf aYd GdMQGQI gh GdJaQjb ef ZjQ GdeJTGHg aGdMQGQI hGdHQhOI hCQLhG Cf jchf cGajkG HYhf Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs